Comparison of GlideScope Video Laryngoscopy and Direct Laryngoscopy for Tracheal Intubation in Neonates. Issue 1 (March 2020) - Tao, B.; Liu, K.; Zhao, P.; Wang, D.; Liu, Y.; Yin, H.
Abstract : ( Anesth Analg . 2019;129(2):482–486) Endotracheal intubation is a common technique for securing the airway and providing ventilation in patients undergoing anesthesia. Today, 2 instruments are available to facilitate this intubation: the classic direct laryngoscope (DL), and the newer GlideScope video laryngoscope (GS). Compared with DL, the GS has been reported to provide a better view of the glottis and helps to decrease the time to intubation (TTI) and improve first attempt success rates compared with DL. While GS has been studied in adults and pediatric patients, no studies have assessed its use in neonates. The aim of this study was to compare the TTI using either DL or GS for endotracheal intubation in neonates.